2017
DOI: 10.1021/jacs.7b09164
|View full text |Cite
|
Sign up to set email alerts
|

Understanding a Hydroformylation Catalyst that Produces Branched Aldehydes from Alkyl Alkenes

Abstract: This paper reports experimental and computational studies on the mechanism of a rhodium-catalyzed hydroformylation that is selective for branched aldehyde products from unbiased alkene substrates. This highly unusual selectivity relies on a phospholane-phosphite ligand prosaically called BOBPHOS. Kinetic studies using in situ high pressure IR (HPIR) and the reaction progress kinetic analysis methodology suggested two steps in the catalytic cycle were involved as turnover determining. Negative order in CO and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 70 publications
3
44
0
Order By: Relevance
“…As shown in Fig. 5 , the alkene insertion step was computed to be the rate-determining step, which is in agreement with the previous computational studies 51 56 and no observation of the H/D scrambling from the product (Fig. 7 ).…”
Section: Resultssupporting
confidence: 89%
“…As shown in Fig. 5 , the alkene insertion step was computed to be the rate-determining step, which is in agreement with the previous computational studies 51 56 and no observation of the H/D scrambling from the product (Fig. 7 ).…”
Section: Resultssupporting
confidence: 89%
“…Rh catalysts with bidentate ligands dominate the scene, especially with substrates with directing groups 22 . At present, the branched-selective hydroformylation of olefins without directing groups is still challenging and can be achieved only by complex Rh catalysts with a selectivity for 2-methylhexanale from 1hexene up to 75% 23,24 and up to 86% for 2-methylbutanale from 1-butene 25 . Supramolecular chemistry has also been used to tune regioselectivity in Rh-catalysed hydroformylation [26][27][28] .…”
mentioning
confidence: 99%
“…In recent work, Clarke et al performed a computational study involving the hydroformylation of styrene catalyzed by a Rh‐BOBPHOS catalyst. [ 63 ] This study also investigated the possible origins of the regioselectivity observed in the reaction and identified, from a noncovalent interaction descriptor (NCI), that C‐H ··· π interactions between the olefin and specific phenyl rings of BOBPHOS are a possible factor responsible by the selectivity. Their main conclusion about the influence of C‐H ··· π interactions into the selectivity is that this interaction plays an essential role as a stabilizing factor.…”
Section: Resultsmentioning
confidence: 99%